Multi-joint isometric measurement for the evidence-based assessment of upper limb strength impairment in wheelchair athletes with different health conditions: a preliminary study - Marta Domínguez-Díez; Javier Raya-González; Jose Elvira; Raul Reina (Termedia Publishing House, 2022)
The present study presents a novel specific multi-joint isometric test to assess upper limb strength impairment for evidence-based classification in wheelchair sports. Sixteen wheelchair athletes participated in this study and were classified according to their type of physical impairment and health condition as follows: athletes with neurological impairment (ANI, n = 5) and athletes with impaired muscle power (IMP, n = 11). In addition, six non-disabled participants formed a control group (CG, n = 6). All the participants performed the isometric propulsion strength test (IPST), evaluating pushing and pulling actions, and two wheelchair performance tests. Excellent relative intra-session reliability scores were obtained for strength values for the ANI, IMP and CG groups (0.90 < ICC < 0.99) and absolute reproducibility showed acceptable scores of SEM (< 9.52%) for IPST pushing action. The ANI had significantly lower scores in strength and wheelchair performance than the IMP and the CG, while no differences were found between the IMP and the non-disabled participants. In addition, no correlations were found for wheelchair athletes between the isometric upper limb strength measure and wheelchair performance. Our findings suggest that the IPST is a valid test for strength measurement in upper limb impairment wheelchair athletes with different health conditions, which must be used in combination with a performance test to obtain a holistic assessment of this population.